POTENSI ARSITEKTUR TRADISIONAL JOGLO SEBAGAI SUMBER BELAJAR SEJARAH ARSITEKTUR DALAM PEMBELAJARAN ILMU PENGETAHUAN SOSIAL - Arrazaq, Naufal Raffi; Juliarman Hatta, Asta; Fitriani, Dara (UHN IGB Sugriwa Denpasar, 2025)
The purpose of the study was to analyze joglo traditional architecture as a source of learning architectural history in social studies subjects. The method used in this study is qualitative. The results showed that the term joglo can be known in Javanese manuscripts such as Kawruh Kalang by R. Sosrowiryatmo and Serat Kawruh Kambeng. Joglo traditional architecture, one of which was used by the Mataram Islam Kingdom around the XVII century AD. Traditional joglo architecture has a profane and sacred function in Javanese culture. Based on architectural, historical, and cultural studies, data on traditional joglo architecture was obtained which has the potential to be used as a source of learning architectural history in social studies subjects. The integration of traditional joglo architecture material content as a source of learning architectural history in social studies subjects is carried out in several steps, namely identifying social studies subject KD, formulating learning objectives and indicators, reviewing material content in joglo traditional architecture, designing learning models and media, and conducting learning evaluations.